2016
DOI: 10.1172/jci.insight.87023
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 substrate release in proximal tubule drives kidney fibrosis

Abstract: Kidney fibrosis following kidney injury is an unresolved health problem and causes significant morbidity and mortality worldwide. In a study into its molecular mechanism, we identified essential causative features. Acute or chronic kidney injury causes sustained elevation of a disintegrin and metalloprotease 17 (ADAM17); of its cleavage-activated proligand substrates, in particular of pro-TNFα and the EGFR ligand amphiregulin (pro-AREG); and of the substrates’ receptors. As a consequence, EGFR is persistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
118
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 69 publications
10
118
0
Order By: Relevance
“…Previously, it has been shown that the shedding of EGFR ligands induces expression and activation of these same ligands in a feed‐forward loop . Il10 −/− / Rhbdf2 −/− mice showed enhanced expression levels of EGFR ligands, suggesting that RHBDF2/ADAM17‐independent shedding events of EGFR ligands such as TGFA by the related RHBDF1/ADAM17, may be sufficient to induce EGFR ligand expression for epithelial repair in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that the shedding of EGFR ligands induces expression and activation of these same ligands in a feed‐forward loop . Il10 −/− / Rhbdf2 −/− mice showed enhanced expression levels of EGFR ligands, suggesting that RHBDF2/ADAM17‐independent shedding events of EGFR ligands such as TGFA by the related RHBDF1/ADAM17, may be sufficient to induce EGFR ligand expression for epithelial repair in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The common regulator of TNF-α and EGFR ligands, ADAM17, has been considered as a potential therapeutic target for chronic kidney diseases, particularly progressive fibrosis (15)(16)(17). In diseased Fcgr2b -/-kidneys, both ADAM17 and iRhom2 were upregulated, and iRhom2 was overexpressed in the kidneys of LN patients.…”
Section: Rhbdf2mentioning
confidence: 99%
“…Although blocking ADAM17 could simultaneously shut down multiple pathogenic pathways and has been proposed for treating chronic kidney diseases not related to LN (15)(16)(17), there are substantial concerns about therapeutically targeting ADAM17, mainly because ADAM17 has an essential role in protecting the skin and intestinal barrier through activating the EGFR pathway (18,19). Indeed, mice lacking Adam17 die at birth due to defects in EGFR signaling, and individuals with ADAM17 mutation or those treated with EGFR inhibitors display skin and intestinal inflammation (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Methods: 502 SLE patients were assessed for serum IFNa level using a biological functional assay(1). Remission was defined by the absence of clinical manifestation of lupus activity (clinical SELENA-SLEDAI = 0) and a prednisone intake £ 5 mg/day (2). Patients in remission were subsequently followed for one year.…”
mentioning
confidence: 99%
“…Interestingly, AREG expression was shown to be one of the most highly upregulated transcripts in peripheral blood leukocytes of patient with systemic lupus erythematosus (SLE) [1]. The functional role of AREG in SLE, and inflammation in general, remains unclear to date and both, pro-and anti-inflammatory functions have been postulated [2,3]. Objectives: Our aim was to investigate the role of AREG in the mouse model of pristane induced lupus (PIL) with particular focus on lupus nephritis (LN).…”
mentioning
confidence: 99%